Mental Health, Work Presenteeism, and Exercise in Inflammatory Bowel Disease. (3rd March 2022) - Sciberras, Martina; Karmiris, Konstantinos; Nascimento, Catarina; Tabone, Trevor; Nikolaou, Penelope; Theodoropoulou, Angeliki; Mula, Abigail; Goren, Idan; Yanai, Henit; Amir, Hadar; Mantzaris, Gerassimnos J; Georgiadi, Tereza; et al.
Abstract: Background: Chronic diseases, such as IBD, can lead to anxiety and depression which can have a significant impact on productivity at work [presenteeism]. The aim of this study was to assess the prevalence of depression/anxiety, presenteeism and exercise levels among IBD patients. Methods: This was a multicentre study whereby adult IBD patients, in clinical remission, were asked to answer a questionnaire anonymously. Hospital Anxiety and Depression Score [HADS], Stanford Presenteeism Scale [SPS-6] and Godin Exercise Score were also collected. Results: A total of 585 patients were recruited. The majority had Crohn's disease [CD, 62.2%] and were male [53.0%], with a median age of 39 years [IQR 30-49]. A psychiatric diagnosis was present in 10.8% of patients prior to their IBD diagnosis. A further 14.2% of patients were psychiatrically diagnosed after IBD diagnosis, this being commoner in CD patients [41.6% of CD, p <0.01]. A raised HADS-Anxiety or a HADS-Depression score ≥8 was present in 46.1% of patients, with 27.4% having a score ≥11. Low presenteeism at work was present in 34.0%. Patients diagnosed with depression/anxiety had a more sedentary lifestyle [ p <0.01], lower presenteeism at work [ p <0.01] and a higher rate of unemployment [ p <0.01]. Conclusions: A significant percentage of IBD patients in remission suffer from anxiety and/or depression. Risk factors for these are CD, female gender, use of biologic medications, long-standing and/or perianal disease. Depression/anxiety was associated with a sedentary lifestyle, lower presenteeism at work and unemployment. Validated screening tools and appropriate referrals to psychologists and/or psychiatrists should be employed within IBD clinics.